2014
DOI: 10.1371/journal.pone.0101413
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Topsoil Encourages Ecological Restoration on Embankments: Soil Fertility, Microbial Activity and Vegetation Cover

Abstract: The construction of linear transport infrastructure has severe effects on ecosystem functions and properties, and the restoration of the associated roadslopes contributes to reduce its impact. This restoration is usually approached from the perspective of plant cover regeneration, ignoring plant-soil interactions and the consequences for plant growth. The addition of a 30 cm layer of topsoil is a common practice in roadslope restoration projects to increase vegetation recovery. However topsoil is a scarce reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 72 publications
1
30
0
Order By: Relevance
“…Addition of topsoil to the original substrate in embankment will increase soil fertility and this improvement will depend on the depth of the topsoil added to the original substrate. Organic matter content, total nitrogen and assimilable phosphorus were all higher in topsoil in comparison with original embankment substrate (Rivera et al, 2014). Generally, 0/100cm (T 1 ) recorded least values throughout the study.…”
Section: Soil Depth and Age On Growth Of Tree Speciesmentioning
confidence: 80%
See 2 more Smart Citations
“…Addition of topsoil to the original substrate in embankment will increase soil fertility and this improvement will depend on the depth of the topsoil added to the original substrate. Organic matter content, total nitrogen and assimilable phosphorus were all higher in topsoil in comparison with original embankment substrate (Rivera et al, 2014). Generally, 0/100cm (T 1 ) recorded least values throughout the study.…”
Section: Soil Depth and Age On Growth Of Tree Speciesmentioning
confidence: 80%
“…(2008) found that increasing soil volume enhances biodiversity effects on plant production. According to Rivera et al (2014), topsoil application enhanced species richness of restored embankment in relation to control. However, the depth of the spread topsoil did not significantly affect resulting plant cover, species richness or floristic composition (Rivera et al, 2014).…”
Section: Plant Diversity In Relation To Stockpile Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…topsoil) in restoration of degraded semi-arid areas (Machado et al, 2013;Muñoz-Rojas et al, 2006b;Rivera et al, 2014). Muñoz-Rojas et al (2016b) showed that soil functions in a rehabilitated area of northwest Western Australia, with the use of mine waste material, can reach levels of microbial activity and organic C similar to those of topsoil once vegetation was established.…”
Section: Implications For Restoration Of Degraded Landsmentioning
confidence: 99%
“…During open-cut and strip mining operations, the top layer of soil is commonly removed and stockpiled before starting the extraction process and then respread before seeding the target sites for restoration (Lamb et al, 2015;Rivera et al, 2014). This topsoil is an important source of seeds, nutrients and microorganisms Golos and Dixon, 2014;Koch, 2007;Muñoz-Rojas et al, 2016b) but its use in restoration is often limited by its scarcity and the detrimental conditions that topsoil stockpiling can have on soil functionality (Keipert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%